Wideband Polarization Conversion Metasurface for RCS Reduction of Antennas - Tao Hong; Ke Peng; Yue Gu; Wen Jiang; Shuxi Gong (International Journal of Antennas and Propagation)
Polarization conversion metasurface (PCM) with wide operating band and high polarization conversion ratio is proposed for antenna radar cross-section (RCS) reduction. A 3rd-order quadrate fractal structure (QFS) is designed as the PCM element that the polarization conversion ratio is greater than 80% from 10.45 GHz to 32.15 GHz (relative bandwidth of 101.9%). The PCM is applied in the RCS reduction of microstrip antennas by chessboard-like arrangement on the antenna. The performances of the proposed PCM and antenna are studied by measurement and simulation. The results show that, with the radiation performance hold, the monostatic RCS of the proposed antenna is obviously reduced from 8 GHz to 28 GHz which completely covers the operating band of the antenna.